Acceptability Of The “Dasunse” Website-Based Learning Media with The Merdeka Learning Pathway in Elementary Schools Across West Java - Astri Nurfauziah; Yunus Abidin; Dede Tri Kurniawan (CV. Ksatria Siliwangi, 2026)
The development of digital technology has encouraged the use of interactive learning media such as Wordwall and Crossword Labs in the teaching and learning process. This study aims to evaluate the level of usability of the two applications using the System Usability Scale (SUS) method. The SUS method was chosen because of its ease and effectiveness in measuring user satisfaction with the system. Data were collected through the SUS questionnaire from respondents who had used both applications in the learning context. The instrument used was the SUS questionnaire consisting of 10 statement items. The study was conducted with a descriptive quantitative approach to 85 teacher respondents. The results showed that the average SUS score for Wordwall and Crossword Labs was 86, which was in the